Legal Protection for Consumers Regarding the Distribution of Cosmetics Containing Hazardous Dyes Under the Consumer Protection Act (Case Study: BPOM Findings from 2025) - Adinda Rahma Kayla Anwar; Yuniar Rahmatiar; Muhamad Abas (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The circulation of cosmetics containing hazardous dyes remains a serious problem in Indonesia despite being regulated under Law No. 8 of 1999 on Consumer Protection. Based on findings by the Indonesian Food and Drug Administration (BPOM) in 2025, cosmetic products containing hazardous substances that pose potential health risks to consumers are still being found. This study aims to analyze the government’s role through the BPOM in overseeing the circulation of cosmetics containing hazardous dyes, as well as to analyze the form of liability of business operators for consumer losses based on Articles 4, 7, 8, 19, 29, and 30 of Law No. 8 of 1999 on Consumer Protection. The research method used is a normative legal approach with a legislative and conceptual framework, utilizing secondary data comprising primary, secondary, and tertiary legal sources through a literature review. The research findings indicate several issues in the oversight of hazardous cosmetics, namely the suboptimal post-market supervision of products circulating in digital media, weak oversight of product distribution in regional areas, and the persistent discrepancy between the registered product composition and the products actually circulating in the market. Furthermore, business operators continue to violate regulations by selling products containing hazardous dyes despite existing prohibitions in the law. Businesses fulfill their responsibilities through product recalls, suspension of distribution, revocation of marketing authorizations, and compensation for consumers. Therefore, it is necessary to strengthen BPOM oversight, enhance monitoring of digital distribution, and enforce the law more rigorously to ensure optimal consumer protection.